Using Health Information Technology to Foster Engagement: Patients' Experiences with an Active Patient Health Record. Issue 3 (4th March 2017) - Rief, John J.; Hamm, Megan E.; Zickmund, Susan L.; Nikolajski, Cara; Lesky, Dan; Hess, Rachel; Fischer, Gary S.; Weimer, Melissa; Clark, Sunday; Zieth, Caroline; Roberts, Mark S.
ABSTRACT: Personal health records (PHRs) typically employ "passive" communication strategies, such as non-personalized medical text, rather than direct patient engagement in care. Currently there is a call for more active PHRs that directly engage patients in an effort to improve their health by offering elements such as personalized medical information, health coaches, and secure messaging with primary care providers. As part of a randomized clinical trial comparing "passive" with "active" PHRs, we explore patients' experiences with using an "active" PHR known as HealthTrak. The "passive" elements of this PHR included problem lists, medication lists, information about patient allergies and immunizations, medical and surgical histories, lab test results, health reminders, and secure messaging. The active arm included all of these elements and added personalized alerts delivered through the secure messaging platform to patients for services coming due based on various demographic features (including age and sex) and chronic medical conditions. Our participants were part of the larger clinical trial and were eligible if they had been randomized to the active PHR arm, one that included regular personalized alerts. We conducted focus group discussions on the benefits of this active PHR for patients who are at risk for cardiovascular disease. Forty-one patients agreed to participate and were organized into five separate focus group sessions. Three main themes emerged from the qualitatively analyzed focus groups: participants reported that the active PHR promoted better communication with providers; enabled them to more effectively partner with their providers; and helped them become more proactive about tracking their health information. In conclusion, patients reported improved communication, partnership with their providers, and a sense of self-management, thus adding insights for PHR designers hoping to address low adoption rates and other patient barriers to the development and use of the technology.